Relating planner task performance for container terminal operations to multi-tasking skills and personality type. (November 2017) - Kurapati, Shalini; Lukosch, Heide; Eckerd, Stephanie; Verbraeck, Alexander; Corsi, Thomas
Highlights: Our study demonstrates the positive and significant effect of multi-tasking ability on operator performance. 'Openness to experience' negatively moderates the impact of multi-tasking ability on operator performance. Females participants outperform their male counterparts in the planning tasks of terminal operations. Managers can benefit from considering our results while allocating tasks to operators or new-recruits. The gaming tools used in this research could be used for evaluating candidate planners. Abstract: Planning the operations within a container terminal is a complex task. It requires planners to demonstrate adaptive behavior while handling stressful, complex, and unexpected situations in today's dynamic and technology dependent workplace. This paper aims at investigating the role of multi-tasking ability, moderated by an individual's personality type, in predicting planner task performance using simulation gaming methods. Hierarchical regression analysis results demonstrate that the direct effect of multi-tasking ability on performance is positive and significant. With one exception, the personality traits do not significantly intensify or lessen the impact of multi-tasking in predicting task performance. The personality trait, openness to experience, significantly lessens the impact of multi-tasking ability on performance. Our results suggest that container terminal operators may benefit by considering the above-mentioned results while allocating planning tasks to their employees and new recruits. The instruments used in this research could also be used for evaluating and training candidate planners.